Proceedings of the 2019 Conference of the North 2019
DOI: 10.18653/v1/n19-1216
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Task Ordinal Regression for Jointly Predicting the Trustworthiness and the Leading Political Ideology of News Media

Abstract: In the context of fake news, bias, and propaganda, we study two important but relatively under-explored problems: (i) trustworthiness estimation (on a 3-point scale) and (ii) political ideology detection (left/right bias on a 7-point scale) of entire news outlets, as opposed to evaluating individual articles. In particular, we propose a multi-task ordinal regression framework that models the two problems jointly. This is motivated by the observation that hyper-partisanship is often linked to low trustworthines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 36 publications
0
37
0
Order By: Relevance
“…Ideology detection in general could be naturally divided into two directions, based on the targets to predict: of the politicians [7,24,28], and of the ordinary citizens [1, 2, 5, 8, 13, 15-17, 20, 23, 29]. The work conducted on ordinary citizens could also be categorized into two types according to the source of data being used: intentionally collected via strategies like survey [1,20], and directly collected such as from news articles [2] or from social networks [13,15,17]. Some studies take advantages from both sides, asking self-reported responses from a group of users selected from social networks [29], and some researchers admitted the limitations of survey experiments [23].…”
Section: Related Work 21 Ideology Detectionmentioning
confidence: 99%
See 3 more Smart Citations
“…Ideology detection in general could be naturally divided into two directions, based on the targets to predict: of the politicians [7,24,28], and of the ordinary citizens [1, 2, 5, 8, 13, 15-17, 20, 23, 29]. The work conducted on ordinary citizens could also be categorized into two types according to the source of data being used: intentionally collected via strategies like survey [1,20], and directly collected such as from news articles [2] or from social networks [13,15,17]. Some studies take advantages from both sides, asking self-reported responses from a group of users selected from social networks [29], and some researchers admitted the limitations of survey experiments [23].…”
Section: Related Work 21 Ideology Detectionmentioning
confidence: 99%
“…Some studies take advantages from both sides, asking self-reported responses from a group of users selected from social networks [29], and some researchers admitted the limitations of survey experiments [23]. Emerging from social science, probabilistic models have been widely used for such kinds of analysis since the early 1980s [2,13,28]. On the other hand, on social network datasets, it is quite intuitive trying to extract information from text data to do ideology-detection [5,8,[15][16][17], only a few paid attention to links [9,13].…”
Section: Related Work 21 Ideology Detectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Dong et al (2015) proposed that a trustworthy source is one that contains very few false claims. Recent work has also focused on evaluating the factuality of reporting of entire news outlets (Baly et al, 2018(Baly et al, , 2019. 3 However, none of this work was about QA or cQA.…”
Section: Related Workmentioning
confidence: 99%